خوێندنەوەی دەقی ئەی رەقیبی دڵدار بەپێی میتۆدی گشتگیری - حسین, علی طاهر; محمود, شنۆ محمد (Sulaimani Journal for Humanities, 2018)
This research is a reading of the text (Ai Raqib) (oh seargent) which was written by the kurdish poet (Dildar) according to the integrated approach. Which means the use of more than one critical approach in analyzing the text. Critics have arguments anout this subject. Them supports it and the other rejects it. This research is a descriptive and analytical study that consists of two parts: the first is to shed light on the definition and the concept of critical theory of critical approach. The second section is related to the practical procedure the text is analyzed according to the following approaches: the text title, text preface, expectation and text centralization.